POLITICAL COMMUNICATION MODEL OF DPRD MEMBERS IN AN EFFORT TO MAINTAIN RELATIONSHIP WITH CONSTITUENTS - Deni Daelani (INFOKUM, 2023)
The role of members of the Regional People's Representative Council (DPRD) in fighting for the ideals or aspirations of the people is still a big question for their constituents, apart from carrying out their functions in legislation, budgeting and oversight. DPRD members must also be able to become communicators such as public relations (PR) in order to establish relationships with their constituents. How the political communication model of DPRD members in maintaining relations with constituents is the main study in this research. By taking the research location in Tasikmalaya district, using descriptive qualitative research methods through data sources from informants or sources from members of the Tasikmalaya Regency DPRD which was carried out by purposive sampling, data collection techniques were interviews, observation and documentation. The results of the discussion in maintaining relations with constituents are by (1) formal means including recess, even though these activities are considered no longer effective (2) non-formal, political communication is carried out based on the creativity of each DPRD member, including routinely conducting friendly visits and maintaining communication by utilizing various media or face to face and visits to constituents. Compared to other regions, the DPRD of Tasikmalaya Regency, such as the DPRD of West Java Province and Sumedang Regency, is still lagging behind in making programs related to improving image and maintaining relations with constituents.